Barrier laminate and packaging container equipped with said barrier laminate

JP7644897B2Active Publication Date: 2025-03-13DAI NIPPON PRINTING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020163976
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-29
Publication Date
2025-03-13
Estimated Expiration
2040-09-29

AI Technical Summary

Benefits of technology

【0033】 本発明によれば、第1蒸着膜との層間の密着性に優れる多層基材を備え、高いラミネート強度を有する包装容器を作製することができ、極めて高いガスバリア性を有する、バリア性積層体を提供することができる。 また、本発明によれば、該バリア性積層体を備える包装容器を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644897000016
    Figure 0007644897000016
  • Figure 0007644897000017
    Figure 0007644897000017
  • Figure 0007644897000018
    Figure 0007644897000018
Patent Text Reader

Abstract

To provide a barrier laminate which has a multilayer base material excellent in adhesion between a vapor-deposited film and layers and has extremely high gas barrier property.SOLUTION: A barrier laminate 10 has a multilayer base material 11, a first vapor-deposited film 12, an adhesive layer 13 and a sealant layer 14. The multilayer base material 11 is subjected to drawing treatment, the multilayer base material 11 further has at least a polypropylene resin layer 15 and a surface resin layer 16, the surface resin layer 16 contains a resin material having a melting point of 180°C or higher, the first vapor-deposited film 12 is composed of an inorganic oxide, and the sealant layer 14 has a second vapor-deposited film 17 and a sealant base material 18.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a barrier laminate and a packaging container provided with the barrier laminate. [Background technology]

[0002] Conventionally, films made of polyesters such as polyethylene terephthalate (hereinafter also referred to as polyester films) have been used as substrates for constituting laminates used in the manufacture of packaging containers because they have excellent mechanical properties, chemical stability, heat resistance, and transparency, as well as being inexpensive.

[0003] Depending on the contents to be filled into the packaging container, the packaging container may be required to have high gas barrier properties such as oxygen barrier property and water vapor barrier property. To meet this requirement, it is common to form a vapor-deposited film containing alumina, silica, etc. on the surface of a polyester film (Patent Document 1).

[0004] In recent years, there has been a search for resin materials to replace polyester films, and the application of such materials to the substrate of polyolefin films, particularly polypropylene films, has been considered. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2005-053223 A Summary of the Invention [Problem to be solved by the invention]

[0006] The inventors of the present invention were considering using a stretched polypropylene film (hereinafter also referred to as a stretched polypropylene film) instead of the conventional polyester film substrate, when they discovered a new problem that satisfactory gas barrier properties could not be obtained even when a vapor deposition film was formed on the surface of the stretched polypropylene film.

[0007] As a result of further investigations, the present inventors discovered that in packaging containers using a barrier laminate in which a vapor-deposited film is provided on the stretched polypropylene film, a unique phenomenon not seen in conventional barrier laminates using a polyester film base material occurs, namely, delamination occurs between the stretched polypropylene film and the vapor-deposited film, and they came to the knowledge that this phenomenon causes insufficient gas barrier properties.

[0008] The inventors then discovered that by providing a surface resin layer containing a resin material having a melting point of 180°C or higher on the surface of a stretched polypropylene film, the adhesion of the vapor-deposited film formed on the surface resin layer is improved and the gas barrier properties are also improved.

[0009] The inventors also discovered that providing a coating layer containing a resin material having a polar group on the surface of a stretched polypropylene film improves the adhesion of the vapor-deposited film formed on the coating layer and also improves the gas barrier properties.

[0010] The present invention has been made based on such findings, and the problem to be solved by the present invention is to provide a barrier laminate having extremely high gas barrier properties, which is provided with a multilayer base material that has excellent interlayer adhesion with a vapor-deposited film.

[0011] Another problem to be solved by the present invention is to provide a packaging container comprising the barrier laminate. [Means for solving the problem]

[0012] In a first aspect, the barrier laminate of the present invention comprises a multilayer substrate, a first vapor-deposited film, an adhesive layer, and a sealant layer, The multilayer base material is subjected to a stretching treatment, Furthermore, the multilayer base material has at least a polypropylene resin layer and a surface resin layer, The surface resin layer contains a resin material having a melting point of 180° C. or more, the first vapor-deposited film is made of an inorganic oxide; The sealant layer comprises a second vapor-deposited film and a sealant substrate.

[0013] In one embodiment, the polypropylene resin layer and the sealant substrate are made of the same material, which is polypropylene.

[0014] In one embodiment, the second vapor-deposited film is an aluminum vapor-deposited film, and the adhesive layer is an adhesive layer containing a cured product of a composition containing a polyester polyol and an isocyanate compound.

[0015] In one embodiment, the melting point of the resin material is 265° C. or less.

[0016] In one embodiment, the difference between the melting point of the resin material and the melting point of the polypropylene contained in the polypropylene resin layer is 20 to 80°C.

[0017] In one embodiment, the resin material has a polar group.

[0018] In one embodiment, the resin material is one or more resin materials selected from ethylene vinyl alcohol copolymer, polyvinyl alcohol, nylon 6, nylon 6,6, MXD nylon, and amorphous nylon.

[0019] In one embodiment, the resin material is a polyamide.

[0020] In one embodiment, the resin material is ethylene vinyl alcohol.

[0021] In one embodiment, the ratio of the thickness of the surface resin layer to the total thickness of the multilayer substrate is 1% or more and 10% or less.

[0022] In one embodiment, the multi-layer substrate is a co-extruded film.

[0023] In a second embodiment, the barrier laminate of the present invention comprises a multilayer substrate, a first vapor-deposited film, an adhesive layer, and a sealant layer, The multilayer substrate includes at least a polypropylene resin layer and a surface coating layer, The polypropylene resin layer is subjected to a stretching treatment, the surface coating layer contains a resin material having a polar group, the first vapor-deposited film is made of an inorganic oxide; The sealant layer comprises a second vapor-deposited film and a sealant substrate.

[0024] In one embodiment, the polypropylene resin layer and the sealant substrate are made of the same material, which is polypropylene.

[0025] In one embodiment, the second vapor-deposited film is an aluminum vapor-deposited film, and the adhesive layer is an adhesive layer containing a cured product of a composition containing a polyester polyol and an isocyanate compound.

[0026] In one embodiment, the ratio of the thickness of the surface coating layer to the total thickness of the multilayer substrate is 0.08% or more and 20% or less.

[0027] In one embodiment, the surface coating layer has a thickness of 0.02 μm or more and 10 μm or less.

[0028] In one embodiment, the resin material is one or more resin materials selected from ethylene vinyl alcohol copolymer (EVOH), polyvinyl alcohol (PVA), polyester, polyethyleneimine, hydroxyl group-containing (meth)acrylic resin, nylon 6, nylon 6,6, MXD nylon, amorphous nylon, and polyurethane.

[0029] In one embodiment, the surface coat layer is a layer formed using a water-based emulsion or a solvent-based emulsion.

[0030] In one embodiment, the barrier laminate of the present invention further comprises a barrier coat layer between the multilayer substrate and the vapor-deposited film.

[0031] In one embodiment, the barrier laminate of the present invention is used in packaging container applications.

[0032] The packaging container of the present invention is characterized by comprising the above-mentioned barrier laminate. Effect of the Invention

[0033] According to the present invention, it is possible to produce a packaging container having high laminate strength and including a multilayer base material with excellent interlayer adhesion with a first vapor deposition film, and it is possible to provide a barrier laminate having extremely high gas barrier properties. Furthermore, according to the present invention, a packaging container including the barrier laminate can be provided. [Brief description of the drawings]

[0034] [Figure 1] 1 is a schematic cross-sectional view showing one embodiment of a barrier laminate of the present invention. [Diagram 2] 1 is a schematic cross-sectional view showing one embodiment of a barrier laminate of the present invention. [Diagram 3] 1 is a schematic cross-sectional view showing one embodiment of a barrier laminate of the present invention. [Figure 4] 1 is a schematic cross-sectional view showing one embodiment of a barrier laminate of the present invention. [Diagram 5] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a deposition apparatus. [Figure 6] FIG. 1 is a schematic cross-sectional view illustrating one embodiment of a deposition apparatus. [Figure 7] FIG. 11 is a schematic cross-sectional view illustrating another embodiment of a deposition apparatus. [Figure 8] 1 is a schematic cross-sectional view showing one embodiment of a barrier laminate of the present invention. [Figure 9] 1 is a schematic cross-sectional view showing one embodiment of a barrier laminate of the present invention. [Figure 10]1 is a front view showing one embodiment of a packaging container of the present invention. [Figure 11] 1 is a perspective view showing one embodiment of a packaging container of the present invention. [Figure 12] FIG. 2 is a schematic diagram showing an example of a method for measuring laminate strength. [Figure 13] FIG. 2 is a schematic diagram showing an example of a method for measuring laminate strength. [Figure 14] FIG. 13 is a graph showing the change in tensile stress with respect to the distance between a pair of grippers that pull the substrate side and the sealant layer side to measure the laminate strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] (Barrier laminate according to the first embodiment) As shown in FIG. 1 , a barrier laminate 10 of the present invention comprises a multilayer substrate 11, a first vapor-deposited film 12, an adhesive layer 13, and a sealant layer 14. The multilayer substrate 11 comprises at least a polypropylene resin layer 15 and a surface resin layer 16, and the sealant layer 14 comprises a second vapor-deposited film 17 and a sealant substrate 18. In one embodiment, the barrier laminate 10 of the present invention further includes a barrier coat layer 19 between the first vapor-deposited film 12 and the adhesive layer 13, as shown in FIG. In one embodiment, the multilayer substrate 11 includes an adhesive resin layer 20 between the polypropylene resin layer 15 and the surface resin layer 16, as shown in FIG. 4, the barrier laminate 10 includes a multilayer substrate 11, a first vapor-deposited film 12, a barrier coat layer 19 provided on the first vapor-deposited film 12, an adhesive layer 13, and a sealant layer 14. The multilayer substrate 11 includes a polypropylene resin layer 15, an adhesive resin layer 10, and a surface resin layer 16, and the adhesive resin layer 20 is provided between the polypropylene resin layer 15 and the surface resin layer 16. The sealant layer 14 includes a second vapor-deposited film 17 and a sealant substrate 18. In one embodiment, the barrier laminate of the present invention includes an intermediate layer (not shown) between the adhesive layer and the sealant layer.

[0036] In the barrier laminate of the first embodiment, the laminate strength between the multilayer substrate and the first vapor-deposited film is preferably 3 N or more, more preferably 4 N or more, and even more preferably 5.5 N or more, per 15 mm width. The upper limit of the laminate strength of the barrier laminate of the first embodiment may be 20 N or less. The method for measuring the laminate strength of the barrier laminate will be described later in the Examples.

[0037] Conventionally, laminates in which a substrate and a sealant layer are made of different resin materials have been used to manufacture packaging containers. However, since it is difficult to separate the substrate and the sealant layer after collecting used packaging containers, the current situation is that such containers are not actively recycled. By forming the substrate and the sealant layer from the same material, it is not necessary to separate the substrate and the sealant layer, and therefore the recycling suitability can be improved. By constructing the sealant substrate from the same material as the polypropylene resin layer of the multilayer substrate, i.e., polypropylene, there is no need to separate the packaging container into layers after collection, thereby improving its recyclability.

[0038] When the sealant layer is made of polypropylene, the content of polypropylene relative to the total amount of resin materials contained in the barrier laminate of the present invention is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, thereby making it possible to further improve the recyclability of packaging containers produced using the barrier laminate of the present invention.

[0039] Each layer of the barrier laminate of the present invention will now be described.

[0040] (Multilayer base material) The multi-layer substrate comprises at least a polypropylene resin layer and a surface resin layer, and may further comprise an adhesive resin layer between the polypropylene resin layer and the surface resin layer.

[0041] The multi-layer substrate is subjected to a stretching treatment, and the stretching treatment may be uniaxial stretching or biaxial stretching. The stretching ratio of the multilayer base material in the machine direction (MD direction) and the transverse direction (TD direction) is preferably 2 to 15 times, and more preferably 5 to 13 times. By setting the stretching ratio at 2 times or more, the strength and heat resistance of the multi-layered substrate can be further improved, and the printability of the multi-layered substrate can also be improved. From the viewpoint of the breaking limit of the multi-layered base material, the stretching ratio is preferably 15 times or less. Furthermore, when the polypropylene resin layer of the multilayer substrate is made heat-sealable to form a packaging container (e.g., a tube) by sealing with an envelope, the stretching ratio is preferably 2 to 10 times, and more preferably 2.5 to 7 times.

[0042] In one embodiment, it is preferable to perform a stretching treatment so that the tensile strength of the multilayer substrate in the machine direction (MD) is greater than the tensile strength in the transverse direction (TD). By adopting such a constitution, it is possible to impart high ease of tearing in one direction to the packaging container produced from the barrier laminate of the present invention. The tensile strength of the multilayer substrate in the machine direction (MD) is preferably at least 1.05 times, more preferably at least 1.10 times, and even more preferably at least 1.2 times, greater than the tensile strength in the cross direction (TD). The tensile strength in the machine direction (MD direction) can be, for example, 200 MPa or more and 300 MPa or less. In this specification, the tensile strength is measured in accordance with JIS K7127: 1999. As a measuring device, a tensile tester STA-1150 manufactured by Orientec Co., Ltd. can be used. The test piece may be a rectangular film cut from the multilayer substrate with a width of 15 mm and a length of 150 mm. The distance between the pair of chucks holding the test piece at the start of the measurement is 100 mm, and the tensile speed is 300 mm / min. In this application, unless otherwise specified, the environment during the measurement of the tensile strength is a temperature of 23°C and a relative humidity of 50%.

[0043] The surface resin layer of the multilayer substrate may be subjected to a surface treatment, which can improve adhesion to adjacent layers. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.

[0044] (Polypropylene resin layer) The polypropylene resin layer is made of polypropylene and may have a single-layer structure or a multi-layer structure. By providing the multi-layer substrate with a layer made of polypropylene, it is possible to improve the oil resistance of a packaging container produced using the multi-layer substrate.

[0045] The polypropylene contained in the polypropylene resin layer may be any of a homopolymer, a random copolymer, and a block copolymer. A polypropylene homopolymer is a polymer of propylene alone, a polypropylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene (e.g., ethylene, butene-1, 4-methyl-1-pentene, etc.), and a polypropylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of the above-mentioned α-olefin other than propylene. Among these polypropylenes, it is preferable to use homopolymers or random copolymers from the viewpoint of transparency. When the rigidity and heat resistance of the packaging bag are important, it is preferable to use homopolymers, and when the impact resistance and the like are important, it is preferable to use random copolymers. It is also possible to use biomass-derived polypropylene and mechanically or chemically recycled polypropylene.

[0046] The polypropylene content in the polypropylene resin layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0047] The polypropylene resin layer may contain a heat seal modifier, which can improve the heat sealability of the polypropylene resin layer and make it easier to produce a packaging container by sealing an envelope. The heat seal modifier is not particularly limited as long as it has excellent compatibility with the polypropylene constituting the heat seal layer, and examples thereof include olefin copolymers. Furthermore, a conventionally known heat sealing agent may be applied to the surface of the polypropylene resin layer and then dried.

[0048] As long as the properties of the present invention are not impaired, the polypropylene resin layer may contain a resin material other than polypropylene, for example, polyolefins such as polyethylene, (meth)acrylic resins, vinyl resins, cellulose resins, polyamide resins, polyesters, and ionomer resins. Furthermore, within the scope of not impairing the characteristics of the present invention, the polypropylene resin layer may contain additives, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0049] The thickness of the polypropylene resin layer is preferably 10 μm or more and 50 μm or less, and more preferably 10 μm or more and 40 μm or less. By making the thickness of the polypropylene resin layer 10 μm or more, the strength and heat resistance of the multilayer base material can be further improved. Furthermore, by setting the thickness of the polypropylene resin layer to 50 μm or less, the film-forming property and processability of the multi-layered base material can be further improved.

[0050] The polypropylene resin layer may have a printed layer on its surface. The image formed on the printed layer is not particularly limited, and may be a letter, a pattern, a symbol, or a combination thereof. The printing layer on the substrate can be formed using ink derived from biomass, which can further reduce the environmental impact. The method for forming the printed layer is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, and flexographic printing.

[0051] (Surface resin layer) The multilayer substrate has a surface protective layer on a polypropylene resin layer, the surface protective layer containing a resin material having a melting point of 180°C or higher (hereinafter also referred to as a high melting point resin material), and a first vapor deposition film having high adhesion can be formed on the surface resin layer, thereby improving the gas barrier properties. Furthermore, as described later, a packaging container produced using a barrier laminate having the surface resin layer has high laminate strength.

[0052] The melting point of the high melting point resin material is more preferably 185° C. or higher, further preferably 190° C. or higher, and particularly preferably 205° C. or higher. By setting the melting point of the high melting point resin material to 185° C. or higher, the adhesion of the vapor-deposited film can be improved, the gas barrier properties can be improved, and the laminate strength of the packaging container can be improved. From the viewpoint of film-forming properties of the multi-layer substrate, the melting point of the high-melting-point resin material is preferably 265° C. or lower, more preferably 260° C. or lower, and even more preferably 250° C. or lower. In this specification, the melting point can be measured in accordance with JIS K7121:2012 (Method for measuring transition temperature of plastics). Specifically, the melting point can be determined by measuring a DSC curve at a temperature rise rate of 10° C. / min using a differential scanning calorimeter (DSC).

[0053] The difference between the melting point of the high melting point resin material contained in the multilayer base material and the melting point of the polypropylene contained in the polypropylene resin layer is preferably 20 to 80°C, and more preferably 20 to 60°C. By setting the difference between the melting point of the high melting point resin material contained in the multi-layer base material and the melting point of the polypropylene contained in the polypropylene resin layer to 20° C. or more, the adhesion of the vapor-deposited film can be improved, the gas barrier properties can be improved, and the laminate strength of the packaging container can be improved. In addition, by making the difference between the melting point of the high melting point resin material contained in the multi-layer base material and the melting point of the polypropylene contained in the polypropylene resin layer 80° C. or less, the film-forming properties of the multi-layer base material can be further improved.

[0054] The high melting point resin material preferably has a polar group. In the present invention, the polar group refers to a group containing one or more heteroatoms, and examples thereof include an ester group, an epoxy group, a hydroxyl group, an amino group, an amide group, a carboxyl group, a carbonyl group, a carboxylic anhydride group, a sulfone group, a thiol group, and a halogen group. Among these, from the viewpoint of the gas barrier properties and laminate strength of the packaging container, hydroxyl groups, ester groups, amino groups, amide groups, carboxyl groups and carbonyl groups are preferred, and amide groups are more preferred.

[0055] The high melting point resin material can be used without any particular limitation as long as it has a melting point of 180° C. or higher, and examples thereof include vinyl resins, polyamides, polyimides, polyesters, (meth)acrylic resins, cellulose resins, polyolefin resins, and ionomer resins.

[0056] In the present invention, resin materials having a melting point of 180° C. or higher and having a polar group are particularly preferred, and polyamides such as ethylene-vinyl alcohol copolymers, polyvinyl alcohol, polyester, nylon 6, nylon 6,6, MXD nylon, and amorphous nylon are preferred. By using such a resin material, the adhesion of the evaporated film formed on the surface resin layer can be significantly improved, and the gas barrier properties can be effectively improved.

[0057] In one embodiment, the high melting point resin material is more preferably an ethylene-vinyl alcohol copolymer. By using an ethylene-vinyl alcohol copolymer as the high melting point resin material, it is possible to suppress a decrease in the gas barrier property even when the barrier laminate is bent.

[0058] In one embodiment, the high melting point resin material is preferably polyamide. By using polyamide as the high melting point resin material, it is possible to suppress the deterioration of the gas barrier property even if the barrier laminate is bent, and when the barrier laminate is used to prepare a packaged product, it is possible to suppress the deterioration of the gas barrier property even if heating such as heat sealing is performed. The high melting point resin material is more preferably nylon 6.

[0059] The content of the high melting point resin material in the surface resin layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0060] As long as the characteristics of the present invention are not impaired, the surface resin layer may contain a resin material other than the high melting point resin material. Furthermore, within the scope of not impairing the characteristics of the present invention, the surface resin layer may contain additives, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0061] The ratio of the thickness of the surface resin layer to the total thickness of the multilayer base material is preferably 1% or more and 10% or less, and more preferably 1% or more and 5% or less. By making the ratio of the thickness of the surface resin layer to the total thickness of the multilayer base material 1% or more, the adhesion of the vapor-deposited film can be improved, the gas barrier properties can be improved, and the laminate strength of the packaging container can be improved. In addition, by making the ratio of the thickness of the surface resin layer to the total thickness of the multilayer substrate 10% or less, the film-forming property and processability of the multilayer substrate can be further improved. In addition, as described later, the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene can be improved.

[0062] The thickness of the surface resin layer is preferably 0.1 μm or more and 5 μm or less, and more preferably 0.1 μm or more and 4 μm or less. By making the thickness of the surface resin layer 0.1 μm or more, the adhesion of the vapor-deposited film can be improved, the gas barrier property can be improved, and the laminate strength of the packaging container can be improved. In addition, by making the thickness of the surface resin layer 5 μm or less, the film-forming property and processing suitability of the multi-layer substrate can be further improved, and as described later, the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene can be improved.

[0063] (adhesive resin layer) In one embodiment, the multi-layer substrate may include an adhesive resin layer between the polypropylene resin layer and the surface resin layer, thereby improving the adhesion between these layers.

[0064] The adhesive resin layer can be formed by using an adhesive resin such as polyether, polyester, silicone resin, epoxy resin, polyurethane, vinyl resin, phenol resin, polyolefin, or an acid-modified product of polyolefin. Of the above, and as will be described later, from the viewpoint of the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene, polyolefins and acid-modified products thereof are preferred, and polypropylene and acid-modified products thereof are particularly preferred. As the adhesive polypropylene, commercially available products can be used, for example, the Admer series manufactured by Mitsui Chemicals, Inc. can be used.

[0065] The thickness of the adhesive resin layer is not particularly limited, but can be, for example, 1 μm or more and 15 μm or less. By making the thickness of the adhesive resin layer 1 μm or more, the adhesion between the polypropylene resin layer and the surface resin layer can be further improved. By making the thickness of the adhesive layer 15 μm or less, the processability of the multi-layered base material can be improved.

[0066] In one embodiment, the multilayer substrate is a co-extruded film, which can be produced by forming a laminated film using a T-die method, an inflation method, or the like, and then stretching the laminated film. By forming the film by the inflation method, the laminated film can be stretched at the same time.

[0067] (First evaporated film) The barrier laminate of the present invention has a first vapor deposition film made of an inorganic oxide on the surface resin layer. This can improve the gas barrier properties of the barrier laminate, specifically, the oxygen barrier properties and water vapor barrier properties. In addition, it can suppress the weight loss of the contents filled in a packaging container made using the barrier laminate of the present invention.

[0068] Examples of inorganic oxides include aluminum oxide (alumina), silicon oxide (silica), magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, barium oxide, and silicon carbide oxide (carbon-containing silicon oxide). Among the above, silica, silicon carbide oxide and alumina are preferred. Moreover, silica is particularly preferable because it does not require aging treatment after the deposition film is formed.

[0069] The thickness of the first vapor-deposited film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. By setting the thickness of the first vapor-deposited film to 1 nm or more, the oxygen barrier property and water vapor barrier property of the barrier laminate can be further improved. In addition, by setting the thickness of the first vapor-deposited film to 150 nm or less, it is possible to prevent the occurrence of cracks in the vapor-deposited film, and as described later, it is possible to improve the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene.

[0070] The deposition film can be formed by a conventional method, for example, physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.

[0071] The vapor-deposited film may be a single layer formed by one vapor deposition process, or a multilayer formed by multiple vapor deposition processes. In the case of a multilayer film, each layer may be made of the same material or different materials. In addition, each layer may be formed by the same method or different methods.

[0072] As an apparatus used in the method for forming a vapor-deposited film by the PVD method, a plasma-assisted vacuum film-forming apparatus can be used. An embodiment of a method for forming a vapor-deposited film using a plasma-assisted vacuum film-forming apparatus will be described below. In one embodiment, the vacuum deposition apparatus includes a vacuum vessel A, an unwinding section B, a deposition drum C, a winding section D, a transport roll E, an evaporation source F, a reactive gas supply section G, an adhesion-preventing box H, a deposition material I, and a plasma gun J, as shown in Figures 5 and 6. 5 is a schematic cross-sectional view of the vacuum film-forming apparatus in the XZ plane, and FIG. 6 is a schematic cross-sectional view of the vacuum film-forming apparatus in the XY plane. 5, the multilayer substrate 11 wound around the film-forming drum C is placed with its surface resin layer surface facing downward in the upper part of the vacuum container A, and an electrically grounded deposition-protection box H is placed below the film-forming drum C in the vacuum container A. An evaporation source F is placed on the bottom surface of the deposition-protection box H. The film-forming drum C is placed in the vacuum container A so that the surface resin layer surface of the barrier laminate 10 wound around the film-forming drum C is located at a position facing the upper surface of the evaporation source F with a certain gap therebetween. In addition, transport rolls E are disposed between the unwinding section B and the film-forming drum C, and between the film-forming drum C and the winding section D. The vacuum vessel is connected to a vacuum pump (not shown). The evaporation source F is for holding the evaporation material I, and is equipped with a heating device (not shown). The reactive gas supply unit G is a portion that supplies a reactive gas (such as oxygen, nitrogen, helium, argon, and a mixture of these gases) that reacts with the evaporated deposition material. The vapor deposition material I is heated and evaporated from the evaporation source F and directed toward the surface resin layer of the multilayer substrate 11, and at the same time, plasma is also directed toward the surface resin layer from the plasma gun J, forming a vapor deposition film. The details of this formation method are disclosed in JP 2011-214089 A.

[0073] As the plasma generating device used in the plasma chemical vapor deposition method, a device generating high frequency plasma, pulse wave plasma, microwave plasma, etc. may be used. Also, a device having two or more film formation chambers may be used. The device is preferably equipped with a vacuum pump so that each film formation chamber can be kept under vacuum. The degree of vacuum in each deposition chamber was 1×10 to 1×10 -6 It is preferred that the value is Pa. An embodiment of a method for forming a vapor-deposited film using a plasma generating device will be described below. First, the multilayer substrate is sent into the deposition chamber and transported at a predetermined speed via an auxiliary roll onto a cooling electrode drum. Next, a mixed gas composition containing a film-forming monomer gas containing an inorganic oxide, oxygen gas, an inert gas, etc. is supplied from the gas supply device into the film-forming chamber, and plasma is generated on the surface resin layer by glow discharge, which is then irradiated to form a vapor-deposited film containing an inorganic oxide on the surface resin layer. The details of this formation method are disclosed in JP2012-076292A.

[0074] FIG. 7 is a schematic diagram showing the configuration of a plasma enhanced chemical vapor deposition apparatus used in a CVD method.

[0075] In one embodiment, as shown in FIG. 7, the plasma chemical vapor deposition apparatus unwinds the multilayer substrate 11 from the unwinding section B1 arranged in the vacuum vessel A1, and further transports the multilayer substrate 11 on the circumferential surface of the cooling / electrode drum C1 at a predetermined speed via the transport roll E1. Oxygen, nitrogen, helium, argon and their mixed gases are supplied from the reactive gas supply G1, and a film-forming monomer gas or the like is supplied from the raw material gas supply section I1. The mixed gas composition for deposition is adjusted and introduced into the vacuum vessel A1 through the raw material supply nozzle H1. Then, plasma is generated by glow discharge plasma F1 on the surface resin layer of the multilayer substrate 11 transported on the circumferential surface of the cooling / electrode drum C1, and the plasma is irradiated to form a deposition film. At this time, a predetermined power is applied to the cooling / electrode drum C1 from the power source K1 arranged outside the vacuum vessel A1, and a magnet J1 is arranged near the cooling / electrode drum C1 to promote the generation of plasma. Next, after forming the vapor-deposited film, the multilayer substrate 11 is wound up at a predetermined winding speed by a transport roll E1 onto a winding section D1. In the drawing, L1 denotes a vacuum pump.

[0076] As an apparatus used in the method for forming a vapor-deposited film, a continuous vapor-deposited film-forming apparatus equipped with a plasma pretreatment chamber and a film-forming chamber can be used. An embodiment of a method for forming a vapor-deposited film using the apparatus will be described below. First, in the plasma pretreatment chamber, plasma is irradiated from a plasma supply nozzle onto the surface resin layer of the multilayer substrate, and then, in the film formation chamber, a vapor deposition film is formed on the plasma-treated surface resin layer. Details of this formation method are disclosed in International Publication WO2019 / 087960.

[0077] The surface of the first vapor-deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.

[0078] In the barrier laminate of the present invention, the first vapor-deposited film is preferably a vapor-deposited film formed by a CVD method, and more preferably a carbon-containing silicon oxide vapor-deposited film formed by a CVD method, which can suppress a decrease in gas barrier properties even when the barrier laminate is bent.

[0079] The carbon-containing silicon oxide vapor-deposited film contains silicon, oxygen, and carbon. In the carbon-containing silicon oxide vapor-deposited film, the proportion C of carbon is preferably 3% or more and 50% or less, more preferably 5% or more and 40% or less, and even more preferably 10% or more and 35% or less, relative to the total of the three elements silicon, oxygen, and carbon, which is 100%. By setting the carbon ratio C in the carbon-containing silicon oxide vapor-deposited film within the above range, deterioration of the gas barrier properties can be suppressed even when the barrier laminate is bent. In this specification, the ratio of each element is based on moles.

[0080] In one embodiment of the carbon-containing silicon oxide vapor-deposited film, the silicon ratio Si is preferably 1% to 45%, more preferably 3% to 38%, and even more preferably 8% to 33%, relative to 100% of the total of the three elements silicon, oxygen, and carbon. The oxygen ratio O is preferably 10% to 70%, more preferably 20% to 65%, and even more preferably 25% to 60%, relative to 100% of the total of the three elements silicon, oxygen, and carbon. By setting the silicon ratio Si and oxygen ratio O in the carbon-containing silicon oxide vapor-deposited film within the above ranges, deterioration of the gas barrier properties can be further suppressed even when the barrier laminate is bent.

[0081] In one embodiment of the carbon-containing silicon oxide vapor-deposited film, the oxygen ratio O is preferably higher than the carbon ratio C, and the silicon ratio Si is preferably lower than the carbon ratio C. The oxygen ratio O is preferably higher than the silicon ratio Si, that is, the ratios are preferably in the order of O, C, and Si. This makes it possible to further suppress the deterioration of the gas barrier properties even when the barrier laminate is bent.

[0082] The proportions C, Si, and O in the carbon-containing silicon oxide vapor-deposited film can be measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the following measurement conditions. (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) X-ray scanning area (measurement area): Approx. 6 mm φ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Etching range: 10mmφ Ion sputtering time: 30 seconds, spectrum collected

[0083] (Adhesive layer) The barrier laminate of the present invention includes an adhesive layer between the evaporated film or the barrier coat layer and the sealant layer, the adhesive layer being provided adjacent to the second evaporated film of the sealant layer.

[0084] The adhesive layer contains at least one adhesive, and may be a one-component curing type, a two-component curing type, or a non-curing type adhesive. The adhesive may be a solvent-free adhesive or a solvent-based adhesive, but from the viewpoint of environmental load, a solvent-free adhesive is preferably used. Examples of solvent-free adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives, and among these, two-component curing urethane adhesives can be preferably used. Examples of the solvent-based adhesive include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.

[0085] When the sealant layer has an aluminum vapor-deposited film as the second vapor-deposited film, the adhesive layer is preferably an adhesive layer containing a cured product of a composition containing a polyester polyol and an isocyanate compound. By configuring the adhesive layer in this way, the oxygen barrier property and water vapor barrier property of the barrier laminate of the present invention can be further improved. Furthermore, when a laminate having a vapor-deposited film is applied to a packaging container, a bending load is usually applied to the laminate by a molding machine or the like, which may cause cracks in the vapor-deposited film. By using an adhesive containing a cured product of a composition containing a polyester polyol and an isocyanate compound, the bending load resistance of the barrier laminate of the present invention can be improved and a decrease in the oxygen barrier property and water vapor barrier property can be suppressed.

[0086] The glass transition temperature of the cured product of the composition containing the polyester polyol and the isocyanate compound is preferably from −30° C. to 80° C., more preferably from 0° C. to 70° C., and even more preferably from 25° C. to 70° C. This can further improve the oxygen barrier property, water vapor barrier property, and laminate strength of the barrier laminate. In this specification, Tg is a value determined by differential scanning calorimetry (DSC) in accordance with JIS K 7121:2012.

[0087] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule. The isocyanate compound has two or more isocyanate groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.

[0088] As a specific example of a composition (adhesive) containing a polyester polyol and an isocyanate compound, the PASLIM series sold by DIC Corporation can be used.

[0089] The composition containing a polyester polyol and an isocyanate compound may further contain a phosphoric acid ester, a plate-like inorganic compound, a coupling agent, cyclodextrin and / or a derivative thereof, and the like.

[0090] As the polyester polyol having two or more hydroxyl groups in one molecule as a functional group, for example, the following [First Example] to [Third Example] can be used. [Example 1] Polyester polyol obtained by polycondensation of ortho-oriented polycarboxylic acid or its anhydride with polyhydric alcohol [Example 2] Polyester polyol with glycerol structure [Example 3] Polyester polyol with isocyanuric ring Each polyester polyol will be described below.

[0091] The polyester polyol according to the first example is a polycondensate obtained by polycondensing a polyvalent carboxylic acid component containing at least one kind of orthophthalic acid and its anhydride, and a polyhydric alcohol component. In particular, polyester polyols in which the content of orthophthalic acid or its anhydride in the total polyvalent carboxylic acid components is 70 to 100 mass % are preferred.

[0092] The polyester polyol according to the first example essentially contains orthophthalic acid and its anhydride as the polycarboxylic acid component, but may be copolymerized with other polycarboxylic acid components as long as the effect of the present embodiment is not impaired. Examples of other polyvalent carboxylic acid components include aliphatic polyvalent carboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecane dicarboxylic acid; unsaturated bond-containing polyvalent carboxylic acids such as maleic anhydride, maleic acid, and fumaric acid; alicyclic polyvalent carboxylic acids such as 1,3-cyclopentane dicarboxylic acid and 1,4-cyclohexane dicarboxylic acid; aromatic polyvalent carboxylic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids; and polybasic acids such as p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Of these, succinic acid, 1,3-cyclopentanedicarboxylic acid, and isophthalic acid are preferred. Two or more of the above other polyvalent carboxylic acids may be used.

[0093] The polyhydric alcohol component includes aliphatic polyhydric alcohols and aromatic polyhydric alcohols. Examples of aliphatic polyhydric alcohols include ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, cyclohexanedimethanol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol. Examples of aromatic polyhydric alcohols include hydroquinone, resorcinol, catechol, naphthalenediol, biphenol, bisphenol A, bisphenol F, tetramethylbiphenol, ethylene oxide extension products of these, and hydrated aliphatic compounds of these. In one embodiment, the polyhydric alcohol component includes at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol.

[0094] As a polyester polyol according to a second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In general formula (1), R1, R2, and R3 each independently represent H (hydrogen atom) or a group represented by the following general formula (2). [ka]

[0095] In formula (2), n represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene groups, 1,2-naphthylene groups, 2,3-naphthylene groups, 2,3-anthraquinonediyl groups, and 2,3-anthracenediyl groups, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 represents a group represented by general formula (2).

[0096] In general formula (1), at least one of R1, R2, and R3 must be a group represented by general formula (2). In particular, it is preferable that all of R1, R2, and R3 are groups represented by general formula (2).

[0097] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (2), a compound in which any two of R1, R2, and R3 are groups represented by general formula (2), and a compound in which all of R1, R2, and R3 are groups represented by general formula (2).

[0098] X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group. When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.

[0099] In the general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.

[0100] The polyester resin compound having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.

[0101] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring, such as a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.

[0102] Examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.

[0103] The polyester polyol according to the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In the general formula (3), R1, R2, and R3 each independently represent "-(CH2)n1-OH (wherein n1 represents an integer of 2 to 4)" or a structure represented by the general formula (4). [ka]

[0104] In the general formula (4), n2 represents an integer of 2 to 4, n3 represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 is a group represented by the general formula (4).

[0105] In the general formula (3), the alkylene group represented by -(CH2)n1- may be linear or branched. Among them, n1 is preferably 2 or 3, and most preferably 2.

[0106] In the general formula (4), n2 represents an integer of 2 to 4; n3 represents an integer of 1 to 5. X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group.

[0107] When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group. The substituent for X is preferably a hydroxyl group, a cyano group, a nitro group, an amino group, a phthalimido group, a carbamoyl group, an N-ethylcarbamoyl group, or a phenyl group, and most preferably a hydroxyl group, a phenoxy group, a cyano group, a nitro group, a phthalimido group, or a phenyl group.

[0108] In the general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.

[0109] In general formula (3), at least one of R1, R2, and R3 is a group represented by general formula (4). Of these, it is preferable that all of R1, R2, and R3 are groups represented by general formula (4).

[0110] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (4), a compound in which any two of R1, R2, and R3 are groups represented by general formula (4), and a compound in which all of R1, R2, and R3 are groups represented by general formula (4).

[0111] The polyester polyol having an isocyanuric ring represented by general formula (3) can be synthesized by reacting a triol having an isocyanuric ring, an aromatic polycarboxylic acid or an anhydride thereof in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.

[0112] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.

[0113] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride, etc. These compounds may have a substituent on any carbon atom of the aromatic ring.

[0114] Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.

[0115] The polyhydric alcohol component may be an alkylene diol having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, or dimethylbutanediol. Among these, polyester polyol compounds having an isocyanuric ring, which use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid as the triol compound having an isocyanuric ring, orthophthalic anhydride as the aromatic polycarboxylic acid or its anhydride in which the carboxylic acid is substituted at the ortho position, and ethylene glycol as the polyhydric alcohol, are particularly preferred in terms of oxygen barrier properties and adhesion.

[0116] The isocyanuric ring is highly polar and trifunctional, and can increase the polarity of the entire system and increase the crosslink density. From this viewpoint, it is preferable that the adhesive resin contains 5% by mass or more of the isocyanuric ring based on the total solid content of the adhesive resin.

[0117] The isocyanate compound has two or more isocyanate groups in the molecule. The isocyanate compound may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by subjecting a known isocyanate blocking agent to an addition reaction by a known, conventional appropriate method. Among these, from the viewpoints of adhesiveness and retort resistance, polyisocyanate compounds having three or more isocyanate groups are preferred, and from the viewpoints of oxygen barrier property and water vapor barrier property, aromatic compounds are preferred.

[0118] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, biurets, and allophanates obtained by reacting these isocyanate compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include polymeric active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.

[0119] The adhesive composed of a cured product of a composition containing a polyester polyol and an isocyanate compound can contain a phosphoric acid-modified compound, for example, a compound represented by the following general formula (5) or (6). [ka] In general formula (5), R1, R2, and R3 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4. [ka] In the formula, R4 and R5 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms and having a (meth)acryloyloxy group, n is an integer of 1 to 4, x is an integer of 0 to 30, and y is an integer of 0 to 30, except for the case where both x and y are 0.

[0120] More specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.

[0121] The content of the phosphoric acid-modified compound in the adhesive layer containing a polyester polyol and an isocyanate compound is preferably from 0.005% by mass to 10% by mass, and more preferably from 0.01% by mass to 1% by mass. By setting the content of the phosphate-modified compound to 0.005% by mass or more, it is possible to improve the oxygen barrier property and the water vapor barrier property, and by setting the content of the phosphate-modified compound to 10% by mass or less, it is possible to improve the adhesion of the adhesive layer.

[0122] The adhesive layer containing a polyester polyol and an isocyanate compound may contain a plate-like inorganic compound, which can improve the oxygen barrier property, water vapor barrier property and adhesiveness of the adhesive layer and can also improve the flex load resistance of the barrier laminate of the present invention. Examples of the plate-like inorganic compounds include kaolinite-serpentine group clay minerals (such as halloysite, kaolinite, endelite, dickite, nacrite, antigorite, and chrysotile) and pyrophyllite-talc group (such as pyrophyllite, talc, and keroli).

[0123] Examples of the coupling agent include silane-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents represented by the following general formula (7). These coupling agents may be used alone or in combination of two or more kinds. [ka]

[0124] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β( aminoethyl) γ-aminopropyl methyl dimethoxysilane, N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylidene).

[0125] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl nor titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and dicumyl phenyl oxyacetate titanate.

[0126] Specific examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer.

[0127] The adhesive formed of the composition containing polyester polyol and an isocyanate compound can contain cyclodextrin and / or its derivatives, which can improve the adhesiveness of the adhesive layer and can further improve the bending load resistance. Specifically, for example, cyclodextrin, alkylated cyclodextrin, acetylated cyclodextrin, hydroxyalkylated cyclodextrin, and the like, in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is substituted with another functional group, can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives may be any of α-cyclodextrin consisting of six glucose units, β-cyclodextrin consisting of seven glucose units, and γ-cyclodextrin consisting of eight glucose units. These compounds may be used alone or in combination of two or more. Hereinafter, these cyclodextrins and / or their derivatives may be collectively referred to as dextrin compounds.

[0128] From the viewpoint of compatibility and dispersibility in the adhesive layer, it is preferable to use a cyclodextrin derivative as the cyclodextrin compound. From the viewpoint of the polarity of the various resins, the degree of substitution is preferably in the range of 0.1 to 14 per glucose atom, and more preferably in the range of 0.3 to 8 per glucose atom.

[0129] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.

[0130] Examples of acetylated cyclodextrin include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, and monoacetyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.

[0131] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.

[0132] The thickness of the adhesive layer is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1 μm or more and 4.5 μm or less. By making the thickness of the adhesive layer 0.5 μm or more, the adhesiveness of the adhesive layer can be improved. In addition, when the adhesive layer is an adhesive layer containing a cured product of a composition containing a polyester polyol and an isocyanate compound, the bending load resistance can be improved. By setting the thickness of the adhesive layer to 6 μm or less, the processability of the barrier laminate can be improved.

[0133] The adhesive layer can be formed by coating or drying a vapor-deposited film or the like using a conventional method such as direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fountain coating, or transfer roll coating.

[0134] (Sealant layer) In the barrier laminate of the present invention, the sealant layer comprises a second vapor-deposited film and a sealant substrate. The barrier laminate of the present invention comprises a sealant layer having such a configuration.

[0135] (Second evaporated film) The second vapor-deposited film is provided on the multilayer substrate side of the sealant layer. The second vapor-deposited film is made of a metal such as aluminum, zirconium, or magnesium, or the above-mentioned metal oxide. Among these, an aluminum vapor deposition film is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. Furthermore, by using an aluminum vapor deposition film, the contents, particularly oil-rich contents, can be effectively prevented from being oxidized due to the transmission of light. The preferred thickness and method of forming the evaporated film are as described above, and therefore will not be described here.

[0136] (Sealant base material) In one embodiment, the sealant base comprises a resinous material that can be fused to one another by heat. Resin materials that can be fused together by heat include, for example, polyolefins such as polyethylene, polypropylene, polybutene, methylpentene polymers, and cyclic olefin copolymers.Specific examples include low-density polyethylene (LDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene (LLDPE), ethylene-α-olefin copolymers polymerized using a metallocene catalyst, and ethylene-propylene copolymers such as random or block copolymers of ethylene and propylene. Examples of resin materials that can be fused to each other by heat include ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl methacrylate copolymer (EMMA), ionomer resins, heat-sealable ethylene-vinyl alcohol resins, acid-modified polyolefins obtained by modifying polyolefins with unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, and itaconic acid, polyesters such as polyethylene terephthalate (PET), polyvinyl acetate resins, poly(meth)acrylic resins, and polyvinyl chloride resins.

[0137] Conventionally, laminates in which a substrate and a sealant layer are made of different resin materials have been used to manufacture packaging containers. However, since it is difficult to separate the substrate and the sealant layer after collecting used packaging containers, the current situation is that such containers are not actively recycled. By forming the substrate and the sealant substrate from the same material, it is not necessary to separate the substrate and the sealant substrate, and the recyclability of the substrate and the sealant substrate can be improved. That is, from the viewpoint of the recyclability of the packaging container produced using the laminate, it is preferable that the sealant substrate is made of polypropylene, among the above-mentioned resin materials. Furthermore, by forming the sealant substrate from polypropylene, the oil resistance of the packaging container produced using the barrier laminate can be improved.

[0138] The sealant base material may contain the above-mentioned heat seal modifier and additives, provided that the characteristics of the present invention are not impaired.

[0139] The sealant base material may have a single-layer structure or a multi-layer structure.

[0140] The thickness of the sealant base material is preferably 15 μm or more and 100 μm or less, and more preferably 20 μm or more and 70 μm or less. By making the thickness of the sealant substrate 15 μm or more, the laminate strength of a packaging container provided with the barrier laminate of the present invention can be further improved. Furthermore, by making the thickness of the sealant substrate 100 μm or less, the processability of the barrier laminate of the present invention can be further improved.

[0141] (Barrier coat layer) The barrier laminate of the present invention may further include a barrier coat layer between the vapor-deposited film and the adhesive layer, thereby improving the oxygen barrier property and water vapor barrier property of the barrier laminate.

[0142] In one embodiment, the barrier coat layer contains a gas barrier resin such as an ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol (PVA), polyacrylonitrile, polyamide such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyester, polyurethane, and (meth)acrylic resin. Among these, polyvinyl alcohol is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. Furthermore, by including polyvinyl alcohol in the barrier coat layer, the occurrence of cracks in the vapor-deposited film can be effectively prevented.

[0143] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more and 95% by mass or less, and more preferably 75% by mass or more and 90% by mass or less. By making the content of the gas barrier resin in the barrier coat layer 50% by mass or more, the oxygen barrier property and water vapor barrier property can be further improved.

[0144] The barrier coat layer may contain the above-mentioned additives to the extent that the characteristics of the present invention are not impaired.

[0145] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By making the thickness of the barrier coat layer 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the barrier laminate can be further improved. By making the thickness of the barrier coat layer 10 μm or less, the processability of the barrier laminate can be improved. In addition, the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene can be improved.

[0146] The barrier coat layer can be formed by dissolving or dispersing the gas barrier resin in water or a suitable solvent, applying the solution, and drying the solution. Alternatively, the barrier coat layer can be formed by applying a commercially available barrier coat agent and drying the solution.

[0147] In another embodiment, the barrier coat layer is a gas barrier coating film containing at least one resin composition such as a hydrolysate of a metal alkoxide or a hydrolyzed condensate of a metal alkoxide obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. By providing such a barrier coat layer on the vapor-deposited film, the occurrence of cracks in the vapor-deposited film can be effectively prevented.

[0148] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.

[0149] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.

[0150] Examples of metal alkoxides satisfying the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).

[0151] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, known organic reactive group-containing organoalkoxysilanes can be used, and in particular, organoalkoxysilanes having epoxy groups are preferred. As organoalkoxysilanes having epoxy groups, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned.

[0152] Two or more of the above silane coupling agents may be used, and the silane coupling agent is preferably used in an amount within the range of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the above metal alkoxides.

[0153] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferred to use these in combination.

[0154] The content of the water-soluble polymer in the gas barrier coating film is preferably 5 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the metal alkoxide. By setting the content of the water-soluble polymer in the gas barrier coating film to 5 parts by mass or more per 100 parts by mass of the metal alkoxide, the oxygen barrier property and water vapor barrier property of the barrier laminate can be further improved. Also, by setting the content of the water-soluble polymer in the gas barrier coating film to 500 parts by mass or less per 100 parts by mass of the metal alkoxide, the film formability of the gas barrier coating film can be improved.

[0155] In the gas barrier coating film, the ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) is preferably 4.5 or less, more preferably 1.0 to 4.5, and even more preferably 1.7 to 3.5, by mass. By setting the ratio of metal alkoxide to water-soluble polymer to be 4.5 or less, deterioration of the gas barrier properties can be suppressed even when the barrier laminate is bent. By setting the ratio of metal alkoxide to water-soluble polymer to be 1.0 or more, deterioration of the gas barrier properties can be suppressed even when heating is performed, such as heat sealing, when a packaged product is produced using the barrier laminate. The above ratio is a solid content ratio.

[0156] The surface of the gas barrier coating film preferably has a ratio of silicon atoms to carbon atoms (Si / C) measured by X-ray photoelectron spectroscopy (XPS) of 1.60 or less, more preferably 0.50 or more and 1.60 or less, and even more preferably 0.90 or more and 1.35 or less. By setting the ratio of silicon atoms to carbon atoms to be 1.60 or less, deterioration of the gas barrier properties can be suppressed even when the barrier laminate is bent. By setting the ratio of silicon atoms to carbon atoms to be 0.50 or more, deterioration of the gas barrier properties can be suppressed even when heating is performed, such as heat sealing, when a packaged product is produced using the barrier laminate. The above range of the ratio of silicon atoms to carbon atoms can be achieved by appropriately adjusting the ratio of the metal alkoxide to the water-soluble polymer. In this specification, the ratio of silicon atoms to carbon atoms is based on moles.

[0157] The ratio of silicon atoms to carbon atoms by X-ray photoelectron spectroscopy (XPS) can be measured by narrow scan analysis under the following measurement conditions. (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) X-ray scanning area (measurement area): Approx. 6 mm φ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Etching range: 10mmφ Ion sputtering time: 30 seconds + 30 seconds + 60 seconds (total 120 seconds) and a spectrum was collected.

[0158] The thickness of the gas barrier coating film is preferably from 0.01 μm to 100 μm, and more preferably from 0.1 μm to 50 μm, which can improve the oxygen barrier property and water vapor barrier property while maintaining recyclability. By making the thickness of the gas barrier coating film 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the barrier laminate can be improved, and the occurrence of cracks in the vapor-deposited film can be prevented. By setting the thickness of the gas barrier coating film to 100 μm or less, the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene can be improved.

[0159] The gas barrier coating film can be formed by applying a composition containing the above-mentioned materials by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coding, or an applicator, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable. As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable, and examples thereof include N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferable. The sol-gel catalyst is preferably used in the range of 0.01 to 1.0 part by mass, and more preferably 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. By using a sol-gel catalyst in an amount of 0.01 part by mass or more per 100 parts by mass of the metal alkoxide, the catalytic effect can be improved, and by using a sol-gel catalyst in an amount of 1.0 part by mass or less per 100 parts by mass of the metal alkoxide, the thickness of the gas barrier coating film formed can be made uniform.

[0160] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for hydrolysis of metal alkoxides, silane coupling agents, and the like. Examples of acids that can be used include mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as acetic acid, tartaric acid, etc. The amount of acid used is preferably 0.001 mol or more and 0.05 mol or less based on the total molar amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. The catalytic effect can be improved by setting the amount of acid to 0.001 moles or more relative to the total molar amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. The thickness of the gas barrier coating film formed can be made uniform by setting the amount of acid to 0.05 moles or less relative to the total molar amount of the metal alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent.

[0161] The composition preferably contains water in an amount of 0.1 to 100 moles, more preferably 0.8 to 2 moles, per mole of the total molar amount of the metal alkoxides. By controlling the water content to 0.1 mole or more per mole of the total molar amount of the metal alkoxides, the oxygen barrier property and water vapor barrier property of the barrier laminate of the present invention can be improved. Also, by controlling the water content to 100 moles or less per mole of the total molar amount of the alkoxides, the hydrolysis reaction can be carried out quickly.

[0162] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.

[0163] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied onto the vapor-deposited film by the above-mentioned conventionally known method and dried. This drying process further advances the polycondensation reaction between the metal alkoxide and the water-soluble polymer (and the silane coupling agent, if the composition contains a silane coupling agent) to form a composite polymer layer. Finally, the composition is heated, for example, at a temperature of 20 to 250° C., preferably 50 to 220° C., for 1 second to 10 minutes, to form a gas barrier coating film.

[0164] The barrier coat layer may have a printed layer formed thereon. The method for forming the printed layer is as described above.

[0165] (Middle class) In one embodiment, the barrier laminate of the present invention includes a middle layer between the adhesive layer and the sealant layer, which can provide stiffness to the barrier laminate of the present invention and improve its strength.

[0166] The intermediate layer contains a resin material, for example, polyolefin, vinyl resin, polyester, (meth)acrylic resin, cellulose resin, etc. Among these, polypropylene is particularly preferable from the viewpoint of the recyclability of the barrier laminate.

[0167] The intermediate layer may contain the above-mentioned additives to the extent that the characteristics of the present invention are not impaired.

[0168] The intermediate layer may have the above-mentioned vapor deposition film or barrier coat layer on its surface.

[0169] The intermediate layer is preferably made of a resin film made of the above-mentioned resin material, and from the viewpoint of strength, the resin film is preferably one that has been subjected to a stretching treatment. The stretching treatment may be uniaxial stretching or biaxial stretching.

[0170] The thickness of the intermediate layer is preferably 10 μm or more and 50 μm or less, and more preferably 10 μm or more and 40 μm or less. By making the thickness of the intermediate layer 10 μm or more, the strength of the barrier laminate can be further improved. Moreover, by making the thickness of the polypropylene resin layer 50 μm or less, the processability of the barrier laminate can be further improved.

[0171] The intermediate layer can be provided via the above-mentioned adhesive layer.

[0172] (Barrier laminate according to the second embodiment) As shown in FIG. 8 , a barrier laminate 21 of the present invention comprises a multilayer substrate 22, a first vapor-deposited film 23, an adhesive layer 24, and a sealant layer 25. The multilayer substrate 22 comprises at least a polypropylene resin layer 26 and a surface coating layer 27, and the sealant layer 25 comprises a second vapor-deposited film 28 and a sealant substrate 29. In one embodiment, the barrier laminate 20 of the present invention further includes a barrier coat layer 30 between the first vapor-deposited film 23 and the adhesive layer 24, as shown in FIG. In one embodiment, the barrier laminate of the present invention includes an intermediate layer (not shown) between the adhesive layer and the sealant layer.

[0173] In the barrier laminate of the second embodiment, the laminate strength between the multilayer substrate and the first vapor-deposited film is preferably 3 N or more, more preferably 4 N or more, and even more preferably 5.5 N or more, per 15 mm width. The upper limit of the laminate strength of the barrier laminate of the second embodiment may be 20 N or less. The method for measuring the laminate strength of the barrier laminate will be described later in the Examples.

[0174] As in the first embodiment, the sealant substrate is preferably made of the same material as the polypropylene resin layer of the multilayer substrate, i.e., polypropylene, which can improve the recyclability of packaging containers produced using the barrier laminate of the present invention.

[0175] When the sealant substrate is made of polypropylene, the content of polypropylene relative to the total amount of resin materials contained in the barrier laminate of the present invention is preferably 80% by mass or more, and more preferably 95% by mass or more, thereby making it possible to further improve the recyclability of packaging containers produced using the barrier laminate of the present invention.

[0176] The multilayer substrate of the barrier laminate of the present invention will be described below. Note that the layers of the barrier laminate of the second embodiment other than the multilayer substrate are the same as those of the barrier laminate of the first embodiment, and therefore will not be described here.

[0177] (Multilayer base material) The multi-layer substrate includes a polypropylene resin layer and a surface coating layer.

[0178] (Polypropylene resin layer) The polypropylene resin layer is made of polypropylene and may have a single-layer structure or a multi-layer structure. By providing the multi-layer substrate with a layer made of polypropylene, it is possible to improve the oil resistance of a packaging container produced using the multi-layer substrate.

[0179] The polypropylene resin layer is a film that has been subjected to a stretching treatment, and the stretching treatment may be uniaxial stretching or biaxial stretching. The stretching ratio in the machine direction (MD direction) and the transverse direction (TD direction) of the polypropylene resin layer is preferably 2 times or more and 15 times or less, and more preferably 5 times or more and 13 times or less. By setting the stretching ratio at 2 times or more, the strength and heat resistance of the polypropylene resin layer can be further improved, and the printability of the polypropylene resin layer can be improved. From the viewpoint of the breaking limit of the polypropylene resin layer, the stretching ratio is preferably 15 times or less.

[0180] The polypropylene contained in the polypropylene resin layer may be any of a homopolymer, a random copolymer, and a block copolymer. A polypropylene homopolymer is a polymer of propylene alone, a polypropylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene (e.g., ethylene, butene-1, 4-methyl-1-pentene, etc.), and a polypropylene block copolymer is a copolymer having a polymer block of propylene and a polymer block of the above-mentioned α-olefin other than propylene. Among these polypropylenes, it is preferable to use homopolymers or random copolymers from the viewpoint of transparency. When the rigidity and heat resistance of the packaging bag are important, it is preferable to use homopolymers, and when the impact resistance and the like are important, it is preferable to use random copolymers. It is also possible to use biomass-derived polypropylene and mechanically or chemically recycled polypropylene.

[0181] The polypropylene content in the polypropylene resin layer is preferably 80% by mass or more, and more preferably 95% by mass or more.

[0182] As long as the properties of the present invention are not impaired, the polypropylene resin layer may contain a resin material other than polypropylene, for example, polyolefins such as polyethylene, (meth)acrylic resins, vinyl resins, cellulose resins, polyamide resins, polyesters, and ionomer resins. Furthermore, within the scope of not impairing the characteristics of the present invention, the polypropylene resin layer may contain additives, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0183] The thickness of the polypropylene resin layer is preferably 10 μm or more and 50 μm or less, and more preferably 10 μm or more and 40 μm or less. By making the thickness of the polypropylene resin layer 10 μm or more, the strength and heat resistance of the multilayer base material can be further improved. Furthermore, by setting the thickness of the polypropylene resin layer to 50 μm or less, the film-forming property and processability of the multi-layered base material can be further improved.

[0184] The polypropylene resin layer may have a printed layer on its surface. The image formed on the printed layer is not particularly limited, and may be a letter, a pattern, a symbol, or a combination thereof. From the viewpoint of environmental impact, the formation of a printed layer on a substrate is preferably carried out using an ink derived from biomass. The method for forming the printed layer is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, flexographic printing, etc. Among these, flexographic printing is preferred from the viewpoint of environmental load.

[0185] The polypropylene resin layer may be subjected to a surface treatment, which can improve the adhesion to the surface coating layer. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.

[0186] (Surface coating layer) The multilayer substrate has a surface coating layer containing a resin material having a polar group on a polypropylene resin layer, and a vapor-deposited film having high adhesion can be formed on the surface coating layer, thereby improving the gas barrier properties. In addition, as described later, a packaging container produced using a barrier laminate having a surface coating layer has high laminate strength.

[0187] The surface coating layer contains a resin material having a polar group. In the present invention, a polar group refers to a group containing one or more heteroatoms, and examples thereof include an ester group, an epoxy group, a hydroxyl group, an amino group, an amide group, a carboxyl group, a carbonyl group, a carboxylic anhydride group, a sulfone group, a thiol group, and a halogen group. Among these, from the viewpoint of lamination properties of the packaging container, a carboxyl group, a carbonyl group, an ester group, a hydroxyl group and an amino group are preferred, and a carboxyl group and a hydroxyl group are more preferred.

[0188] Preferred examples of resin materials having a polar group include ethylene-vinyl alcohol copolymers (EVOH), polyvinyl alcohol (PVA), polyesters, polyethyleneimines, hydroxyl-containing (meth)acrylic resins, polyamides such as nylon 6, nylon 6,6, MXD nylon, and amorphous nylon, and polyurethanes, with polyamides, hydroxyl-containing (meth)acrylic resins, ethylene-vinyl alcohol copolymers, and polyvinyl alcohol being particularly preferred. In one embodiment, the resin material having a polar group is preferably a hydroxyl group-containing (meth)acrylic resin, since this can suppress deterioration of the gas barrier properties even when heating is performed, such as heat sealing, when producing a packaged product using the barrier laminate. By using such a resin material, the adhesion of the evaporated film formed on the surface coating layer can be significantly improved, and the gas barrier properties of the film can be effectively improved.

[0189] In the present invention, the surface coating layer can be formed using an aqueous emulsion or a solvent-based emulsion. Specific examples of the aqueous emulsion include polyamide-based emulsion, polyethylene-based emulsion, and polyurethane-based emulsion, and specific examples of the solvent-based emulsion include polyester-based emulsion.

[0190] The content of the resin material having a polar group in the surface coating layer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0191] As long as the characteristics of the present invention are not impaired, the surface coating layer may contain a resin material other than the resin material having a polar group. Furthermore, within the scope of not impairing the characteristics of the present invention, the surface coating layer may contain additives, such as crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.

[0192] The ratio of the thickness of the surface coating layer to the total thickness of the multilayer substrate is preferably 0.08% or more and 20% or less, more preferably 0.2% or more and 20% or less, preferably 1% or more and 20% or less, and more preferably 3% or more and 10% or less. By setting the ratio of the thickness of the surface coating layer to the total thickness of the multilayer substrate to 0.08% or more, the adhesion of the vapor deposition film can be improved, the gas barrier properties can be improved, and the laminate strength of the packaging container can be improved. In addition, by setting the ratio of the thickness of the surface resin layer to the total thickness of the multi-layered substrate to 20% or less, the processability of the multi-layered substrate can be further improved. In addition, as described below, the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene can be improved.

[0193] The thickness of the surface coating layer is preferably 0.02 μm or more and 10 μm or less, more preferably 0.05 μm or more and 10 μm or less, even more preferably 0.1 μm or more and 10 μm or less, and even more preferably 0.2 μm or more and 5 μm or less. By making the thickness of the surface coating layer 0.02 μm or more, the adhesion of the vapor-deposited film can be improved, the gas barrier property can be improved, and the laminate strength of the packaging container can be improved. In addition, by making the thickness of the surface coating layer 10 μm or less, the processability of the multi-layered substrate can be further improved, and as described later, the recyclability of a packaging container produced using a laminate of the barrier laminate of the present invention and a sealant layer made of polypropylene can be improved.

[0194] The multilayer substrate can be produced offline. Specifically, a resin composition containing polypropylene is formed into a film using a T-die method or an inflation method, etc., to form a resin film, which is then stretched, and a coating liquid for forming a coat is applied onto the resin film and dried to produce the multilayer substrate. The multi-layer substrate can also be produced in-line, specifically, by forming a resin composition containing polypropylene into a film using a T-die method or an inflation method, etc., forming a resin film, stretching the resin film in the machine direction (MD), applying a coating liquid for forming a coat on the resin film, drying the resin film, and then stretching the resin film in the transverse direction (TD). Note that the stretching in the transverse direction may be performed first.

[0195] (packaging container) The packaging container of the present invention is characterized by comprising the above-mentioned barrier laminate. Examples of the packaging container include packaging products (packaging bags), lids, and laminate tubes.

[0196] Examples of packaging bags include packaging bags of various shapes, such as standing pouch type, side seal type, two-sided seal type, three-sided seal type, four-sided seal type, envelope seal type, grommet seal type (pillow seal type), pleated seal type, flat bottom seal type, square bottom seal type, and gusset type.

[0197] As shown in FIG. 10, the packaging container of the present invention is a packaging bag 31 made by bonding two sheets of a barrier laminate together (the shaded areas are the heat-sealed areas). When the tensile strength of the multilayer substrate in the longitudinal direction (MD direction) is greater than the tensile strength in the transverse direction (TD direction), it is preferable to fabricate the packaging bag so that the longitudinal direction (MD direction) of the multilayer substrate corresponds to the transverse direction of the packaging bag 31, and the transverse direction (TD direction) of the multilayer substrate corresponds to the longitudinal direction of the packaging bag 31. This configuration makes it extremely easy to tear the packaging container in the transverse direction. The same applies to the packaging containers exemplified below.

[0198] The packaging container of the present invention is a stand-up pouch 32, as shown in FIG. Fig. 11 is a diagram showing a simplified example of the configuration of a standing pouch. As shown in Fig. 11, a standing pouch 32 is composed of a body portion (side sheets) 33 and a bottom portion (bottom sheet) 34. At least one of the side sheet 33 and the bottom sheet 34 of the standing pouch 32 is made of the barrier laminate of the present invention.

[0199] In one embodiment, the body 33 of the standing pouch 32 can be formed by making a bag so that the sealant layer of the barrier laminate of the present invention becomes the innermost layer. In another embodiment, the side sheet 33 can be formed by preparing two barrier laminates of the present invention, overlapping them with their sealant layers facing each other, inserting two V-shaped laminates into both ends of the overlapped barrier laminate with the sealant layers facing outward, and heat sealing them. This production method can produce a stand-up pouch having a body with side gussets.

[0200] In one embodiment, the bottom sheet 34 of the standing pouch 32 can be formed by inserting the barrier laminate of the present invention between the side sheets of a bag and heat sealing it. More specifically, the barrier laminate can be folded in a V shape with the sealant layer facing outward, inserted between the side sheets of a bag, and heat sealed.

[0201] The packaging container may also be provided with easy-opening means 35 as shown in FIG. Examples of the easy-to-open means 35 include, as shown in FIG. 10, a notch 36 which serves as the starting point for tearing, and a half-cut line 37 formed by laser processing or a cutter as a path for tearing.

[0202] The packaging container may also include a steam release mechanism 38, as shown in Fig. 11. The steam release mechanism 38 is configured to communicate the inside and outside of the packaging container when the steam pressure inside the packaging container reaches or exceeds a predetermined value, to release steam, and to suppress the steam from escaping at places other than the steam release mechanism 38. The steam release mechanism 38 includes a steam release seal portion 38a that protrudes from the side seal portion toward the inside of the packaging container, and a non-seal portion 38b that is isolated from the content-accommodating portion by the steam release seal portion 38a. The non-sealed portion 38b is connected to the outside of the packaging container. When the packaging container, which is filled with the contents and has a heat-sealed opening, is heated in a microwave oven or the like, the internal pressure increases and the steam-sealed portion 38a peels off. Steam passes through the peeled portion of the steam-sealed portion 38a and the non-sealed portion 38b and escapes to the outside of the packaging container.

[0203] The heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.

[0204] The contents filled in the packaging container are not particularly limited, and may be liquid, powder, or gel. In addition, the contents may be food or non-food. EXAMPLES

[0205] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0206] Example 1-1 Polyamide (Ube Industries, Ltd., polyamide 6, melting point: 220 ° C.), adhesive resin (Mitsui Chemicals, Inc., Admer QF500, maleic anhydride modified polypropylene), and polypropylene (Japan Polypropylene, Novatec FL203D, melting point: 160 ° C.) were co-extruded, and then stretched 5 times in the longitudinal direction (MD direction) and 10 times in the transverse direction (TD direction) by a sequential biaxial stretching device to produce a 21 μm thick multilayer substrate having a surface resin layer (0.4 μm) made of polyamide, an adhesive resin layer (1 μm) made of adhesive resin, and a polypropylene resin layer (19.6 μm) made of polypropylene. The ratio of the thickness of the surface resin layer made of polyamide to the layer thickness of the multilayer substrate was 2%.

[0207] On the surface resin layer of the multilayer substrate prepared as described above, a carbon-containing silicon oxide vapor deposition film (first vapor deposition film) having a thickness of 12 nm was formed (CVD method) by a roll-to-roll method using a low-temperature plasma chemical vapor deposition apparatus, while applying tension to the multilayer substrate. The vapor deposition film formation conditions were as follows. (Formation conditions) Hexamethyldisiloxane:oxygen gas:helium=1:10:10 (unit: slm) Cooling / electrode drum power supply: 22kw Line speed: 100m / min

[0208] In the carbon-containing silicon oxide vapor deposition film, the carbon percentage C, silicon percentage Si, and oxygen percentage O were 32.7%, 29.8%, and 37.5%, respectively, based on the total of the three elements silicon, oxygen, and carbon, which is 100%. The percentages of each element were measured by narrow scan analysis using X-ray photoelectron spectroscopy (XPS) under the following measurement conditions. (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) X-ray scanning area (measurement area): Approx. 6 mm φ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Etching range: 10mmφ Ion sputtering time: 30 seconds, spectrum collected

[0209] 385g of water, 67g of isopropyl alcohol, and 9.1g of 0.5N hydrochloric acid were mixed to obtain a solution with a pH of 2.2. 175g of tetraethoxysilane as a metal alkoxide and 9.2g of glycidoxypropyltrimethoxysilane as a silane coupling agent were mixed into this solution while cooling to 10°C to obtain solution A. Solution B was obtained by mixing 14.7 g of polyvinyl alcohol having a saponification degree of 99% or more and a polymerization degree of 2400 as a water-soluble polymer, 324 g of water, and 17 g of isopropyl alcohol. Solution A and solution B were mixed in a ratio of 6.5:3.5 by mass to obtain a barrier coating agent.

[0210] A barrier coating agent was applied by spin coating onto the vapor-deposited film formed on the multi-layer substrate, and the resulting film was subjected to a heat treatment in an oven at 80° C. for 60 seconds to form a barrier coating layer having a thickness of 300 nm.

[0211] As a heat seal layer, an unstretched polypropylene film (manufactured by Mitsui Chemicals Tocello, Inc., 2703) having an aluminum vapor deposition film having a thickness of 450 Å on one side was prepared.

[0212] The barrier coat layer formed as described above and the aluminum vapor deposition film of the heat seal layer were laminated via an adhesive containing polyester polyol and an isocyanate compound (manufactured by DIC Corporation, product name: PASLIM VM001 / VM102CP (mixing ratio 1:1)) and left to stand at 40°C for 48 hours to obtain a barrier laminate of the present invention. The thickness of the adhesive layer formed by the two-component curing adhesive was 1 μm. The polypropylene content in the barrier laminate was 90% by mass.

[0213] Example 1-2 A barrier laminate of the present invention was produced in the same manner as in Example 1-1, except that the adhesive used to form the adhesive layer was changed to a polyurethane adhesive (Takelac A-969V / Takenate A-5 (mixing ratio 3 / 1) manufactured by Mitsui Chemicals, Inc.). The polypropylene content in the barrier laminate was 90% by mass.

[0214] Example 2-1 A solution for forming a surface coating layer having the following composition was applied to the corona-treated surface of a 20 μm-thick biaxially oriented polypropylene film (ME-1, manufactured by Mitsui Chemicals Tocello Co., Ltd.) with one side corona-treated, and then dried to form a surface coating layer with a thickness of 0.5 μm, thereby producing a multilayer substrate. (Coating liquid composition for forming surface coating layer) Polyvinyl alcohol 5% by weight (Nippon Bismuth Poval Co., Ltd., VC-10, polymerization degree 1000, saponification degree 99.3 mol% or more) ·Water 90% by mass Isopropanol (IPA) 5% by weight

[0215] A barrier laminate was produced in the same manner as in Example 1-1, except that the multilayer substrate produced in Example 1-1 was changed to the multilayer substrate produced as described above. The polypropylene content in the barrier laminate was 92% by mass.

[0216] Example 2-2 A barrier laminate was produced in the same manner as in Example 2-1, except that the composition of the coating solution for forming the surface coat layer was changed as follows. The polypropylene content in the barrier laminate was 92% by mass. (Coating liquid composition for forming surface coating layer) ·EVOH 75% by mass (Eversolve #10, manufactured by Nippon Cima Co., Ltd.) ·Water 12.5% ​​by mass 1-Propanol 12.5% ​​by mass

[0217] Example 2-3 A barrier laminate of the present invention was produced in the same manner as in Example 2-1, except that the adhesive used to form the adhesive layer was changed to a polyurethane adhesive (Takelac A-969V / Takenate A-5 (mixing ratio 3 / 1) manufactured by Mitsui Chemicals, Inc.). The polypropylene content in the barrier laminate was 92% by mass.

[0218] Comparative Example 1-1 The above polypropylene (Novatec FL203D, manufactured by Japan Polypropylene Corporation, melting point: 160°C) was extruded and then stretched 5 times in the machine direction (MD) and 10 times in the transverse direction (TD) using a sequential biaxial stretching device to produce a propylene film with a thickness of 20 μm. A barrier laminate was produced in the same manner as in Example 1-1, except that the multi-layer substrate in Example 1-1 was changed to the polypropylene film produced as described above.

[0219] <<Gas barrier property evaluation>> The barrier laminates obtained in the above examples and comparative examples were cut out to obtain test pieces. The test pieces were used to measure the oxygen permeability (cc / m 2 ·day·atm) and water vapor transmission rate (g / m 2 ·day) was measured by the following method, and the results are summarized in Table 1.

[0220] [Oxygen permeability] Using an oxygen permeability measuring device (OX-TRAN2 / 20 manufactured by MOCON), the test piece was set so that the multilayer substrate side was the oxygen supply side, and the oxygen permeability was measured in an environment of 23°C and a relative humidity of 90% RH in accordance with JIS K 7126. [Water vapor permeability] Using a water vapor transmission rate measuring device (MOCON, PERMATRAN-w 3 / 33), the multilayer substrate side of the test piece was set as the water vapor supply side, and the water vapor transmission rate was measured in an environment of 40°C and a relative humidity of 90% RH in accordance with JIS K 7129.

[0221] <<Laminate strength test>> The barrier laminates obtained in the above Examples and Comparative Examples were cut into strips of 15 mm width, and the laminate strength (N / 15 mm) of the cut samples was measured using a tensile tester (Tensilon universal material testing machine, manufactured by Orientec Co., Ltd.) in accordance with JIS K6854-2, at a peel speed of 50 mm / min and 90° peeling (T-peel method). Specifically, first, a strip-shaped test piece 70 was prepared by cutting out the barrier laminate and peeling the substrate side 71 and the sealant layer side 72 by 15 mm in the long side direction as shown in FIG. 12. Then, as shown in FIG. 13, the already peeled portions of the substrate side 71 and the sealant layer side 72 were gripped by grips 73 of a measuring device. The grips 73 were pulled at a speed of 50 mm / min in opposite directions perpendicular to the surface direction of the portions where the substrate side 71 and the sealant layer side 72 are still laminated, and the average value of the tensile stress in the stable region (see FIG. 14) was measured. The interval S between the grips 73 was 30 mm when the pulling started, and the interval S between the grips 73 was 60 mm when the pulling ended. FIG. 14 is a diagram showing the change in tensile stress with respect to the interval S between the grips 73. As shown in FIG. 14, the change in tensile stress with respect to the interval S passes through a first region and enters a second region (stable region) in which the rate of change is smaller than that in the first region. The average value of the tensile stress in the stable region was measured for the five test pieces 70, and the average value was determined as the laminate strength. The measurement was performed in an environment of a temperature of 23° C. and a relative humidity of 50%. The measurement results are summarized in Table 1.

[0222] [Table 1]

[0223] Reference example 1-1 A multi-layer substrate was prepared in the same manner as in Example 1-1, and a vapor-deposited film was formed on the multi-layer substrate.

[0224] A barrier coat layer was formed on the vapor deposition film such that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 5.1 on a mass basis.

[0225] The ratio of Si and C elements present on the barrier coat layer surface was measured. The measurement was performed by narrow scan analysis under the following measurement conditions using X-ray photoelectron spectroscopy (XPS). Note that in the following reference examples, the ratio of Si and C elements present on the barrier coat layer surface was measured in the same manner. (Measurement conditions) Equipment used: "ESCA-3400" (manufactured by Kratos) [1] Spectral collection conditions Incident X-ray: MgKα (monochromatic X-ray, hν=1253.6eV) X-ray output: 150W (10kV 15mA) X-ray scanning area (measurement area): Approx. 6 mm φ Photoelectron capture angle: 90 degrees [2] Ion sputtering conditions Ion species: Ar + Acceleration voltage: 0.2 (kV) Emission current: 20 (mA) Etching range: 10mmφ Ion sputtering time: 30 seconds + 30 seconds + 60 seconds (total 120 seconds) and a spectrum was collected.

[0226] Next, a 60 μm-thick unstretched polypropylene film (P1128, manufactured by Toyobo Co., Ltd.) was dry laminated onto the barrier coat layer with a two-component curing polyurethane adhesive to form a sealant layer, thereby obtaining a barrier laminate.

[0227] Reference example 1-2 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0228] Reference example 1-3 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0229] Reference example 1-4 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0230] Reference example 1-5 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0231] Reference example 1-6 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0232] Reference example 2-1 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the formation of the vapor-deposited film was changed as follows. A continuous vapor deposition film formation device having a pretreatment section in which an oxygen plasma pretreatment device was placed, which was an actual device, and a film formation section separated from each other was used on the surface resin layer. In the pretreatment section, plasma was introduced from a plasma supply nozzle under the conditions described below while applying tension to the multilayer substrate by roll-to-roll movement, and oxygen plasma pretreatment was performed. In the film formation section, which was continuously transported, a 12 nm thick aluminum oxide (alumina) vapor deposition film was formed on the oxygen plasma treated surface under the conditions described below using a reactive resistance heating method as a heating means for vacuum vapor deposition (PVD method). (Formation conditions) (Oxygen plasma pretreatment conditions) Plasma intensity: 200W·sec / m 2 Plasma formation gas ratio: oxygen:argon = 2:1 Voltage applied between pretreatment drum and plasma supply nozzle: 340V (Film formation conditions) -Conveying speed: 400m / min Oxygen gas supply: 20,000sccm

[0233] Reference example 2-2 A barrier laminate was produced in the same manner as in Reference Example 2-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0234] Reference example 2-3 A barrier laminate was produced in the same manner as in Reference Example 2-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0235] Reference example 2-4 A barrier laminate was produced in the same manner as in Reference Example 2-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0236] Reference example 2-5 A barrier laminate was produced in the same manner as in Reference Example 2-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0237] Reference example 2-6 A barrier laminate was produced in the same manner as in Reference Example 2-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0238] Reference example 3-1 A barrier laminate was produced in the same manner as in Reference Example 1-1, except that the polyamide was changed to ethylene vinyl alcohol (Eval F171B, manufactured by Kuraray Co., Ltd., melting point: 183° C.) and a surface resin layer was formed.

[0239] Reference example 3-2 A barrier laminate was produced in the same manner as in Reference Example 3-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0240] Reference example 3-3 A barrier laminate was produced in the same manner as in Reference Example 3-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0241] Reference example 3-4 A barrier laminate was produced in the same manner as in Reference Example 3-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0242] Reference example 3-5 A barrier laminate was produced in the same manner as in Reference Example 3-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0243] Reference example 3-6 A barrier laminate was produced in the same manner as in Reference Example 3-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0244] Reference example 4-1 A barrier laminate was produced in the same manner as in Reference Example 2-1, except that the polyamide was changed to ethylene vinyl alcohol (Eval F171B, manufactured by Kuraray Co., Ltd., melting point: 183° C.) and a surface resin layer was formed.

[0245] Reference example 4-2 A barrier laminate was produced in the same manner as in Reference Example 4-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0246] Reference example 4-3 A barrier laminate was produced in the same manner as in Reference Example 4-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0247] Reference example 4-4 A barrier laminate was produced in the same manner as in Reference Example 4-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0248] Reference example 4-5 A barrier laminate was produced in the same manner as in Reference Example 4-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0249] Reference example 4-6 A barrier laminate was produced in the same manner as in Reference Example 4-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0250] Reference example 5-1 A coating solution for forming a surface coat layer prepared as described below was applied to the corona-treated surface of the biaxially oriented polypropylene film of Example 2-1, and dried to form a surface coat layer having a thickness of 0.5 μm, thereby producing a multilayer substrate.

[0251] A hydroxyl-containing (meth)acrylic resin (number average molecular weight 25,000, glass transition temperature 99°C, hydroxyl value 80 mg KOHL / g) was diluted with a mixed solvent of methyl ketone and ethyl acetate (mixing ratio 1:1) to a solid concentration of 10 mass% to prepare the base resin. A solution of tolylene diisocyanate in ethyl acetate (solid content 75% by mass) was added to the base material as a curing agent to obtain a coating solution for forming a surface coating layer. The amount of the curing agent used was 10 parts by mass per 100 parts by mass of the base material.

[0252] Next, a vapor-deposited film was formed in the same manner as in Example 2-1.

[0253] Next, a barrier coat layer was formed on the vapor deposition film such that the solid content ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 5.1 on a mass basis.

[0254] Next, a 60 μm-thick unstretched polypropylene film (P1128, manufactured by Toyobo Co., Ltd.) was dry laminated onto the barrier coat layer with a two-component curing polyurethane adhesive to form a sealant layer, thereby obtaining a barrier laminate.

[0255] Reference example 5-2 A barrier laminate was produced in the same manner as in Reference Example 5-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0256] Reference example 5-3 A barrier laminate was produced in the same manner as in Reference Example 5-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0257] Reference example 5-4 A barrier laminate was produced in the same manner as in Reference Example 5-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0258] Reference example 5-5 A barrier laminate was produced in the same manner as in Reference Example 5-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0259] Reference example 5-6 A barrier laminate was produced in the same manner as in Reference Example 5-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0260] Reference example 6-1 A second barrier laminate was produced in the same manner as in Reference Example 5-1, except that the deposition film was formed as follows. On the surface coating layer, a silicon oxide (silica) vapor deposition film with a thickness of 20 nm was formed (PVD method) by applying tension to the multilayer substrate by roll to roll using an induction heating vacuum deposition device equipped with a plasma gun. The vapor deposition film formation conditions were as follows: (Formation conditions) (Plasma irradiation conditions) Line speed: 30m / min ·Vacuum degree: 1.7×10 -2 Pa Power: 5.7kw Acceleration voltage: 151V Ar gas flow rate: 7.5sccm (Film formation conditions) Deposition material: SiO Reactive gas: O2 Reaction gas flow rate: 100sccm

[0261] Reference example 6-2 A barrier laminate was produced in the same manner as in Reference Example 6-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0262] Reference example 6-3 A barrier laminate was produced in the same manner as in Reference Example 6-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0263] Reference example 6-4 A barrier laminate was produced in the same manner as in Reference Example 6-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0264] Reference example 6-5 A barrier laminate was produced in the same manner as in Reference Example 6-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0265] Reference example 6-6 A barrier laminate was produced in the same manner as in Reference Example 6-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0266] Reference example 7-1 A barrier laminate was produced in the same manner as in Reference Example 5-1, except that the deposition film was formed as follows.

[0267] A continuous vapor deposition film formation device having a pretreatment section in which an oxygen plasma pretreatment device was placed, which was an actual device, and a film formation section separated from each other was used on the surface coating layer. In the pretreatment section, while tension was applied to the multilayer substrate by roll-to-roll, plasma was introduced from a plasma supply nozzle under the conditions described below to perform oxygen plasma pretreatment. In the film formation section, which was continuously transported, a 12 nm thick aluminum oxide (alumina) vapor deposition film was formed on the oxygen plasma treated surface under the conditions described below using a reactive resistance heating method as a heating means for the vacuum deposition method (PVD method). (Formation conditions) (Oxygen plasma pretreatment conditions) Plasma intensity: 200W·sec / m 2 Plasma formation gas ratio: oxygen:argon = 2:1 Voltage applied between pretreatment drum and plasma supply nozzle: 340V (Film formation conditions) -Conveying speed: 400m / min Oxygen gas supply: 20,000sccm

[0268] Reference example 7-2 A barrier laminate was produced in the same manner as in Reference Example 7-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 4.1 by mass.

[0269] Reference example 7-3 A barrier laminate was produced in the same manner as in Reference Example 7-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 3.3 by mass.

[0270] Reference example 7-4 A barrier laminate was produced in the same manner as in Reference Example 7-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 2.7 by mass.

[0271] Reference example 7-5 A barrier laminate was produced in the same manner as in Reference Example 7-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.9 by mass.

[0272] Reference example 7-6 A barrier laminate was produced in the same manner as in Reference Example 7-1, except that the barrier coat layer was formed so that the solids ratio of the metal alkoxide to the water-soluble polymer (metal alkoxide / water-soluble polymer) was 1.5 by mass.

[0273] <<Gas barrier property evaluation (after lamination)>> The barrier laminate obtained in the above-mentioned Reference Example was cut out to obtain a test piece. Using this test piece, the oxygen permeability (cc / m 2 ·day·atm) and water vapor transmission rate (g / m 2 ·day) was measured. The results are summarized in Tables 2 to 8. Note that in Tables 2 to 8, the units of oxygen permeability and vapor permeability are omitted.

[0274] <<Gas barrier property evaluation (after Gelbo flex test)>> A cylindrical bag was prepared using the barrier layer obtained in the above-mentioned Reference Example, and the Gelbo flex test according to ASTM F392 was repeated 10 times using this bag. Thereafter, a barrier laminate was cut out from the bag to obtain a test piece. The oxygen permeability (cc / m 2 ·day·atm) and water vapor transmission rate (g / m 2·day) was measured. The results are summarized in Tables 2 to 8. Note that in Tables 2 to 8, the units of oxygen permeability and vapor permeability are omitted.

[0275] [Table 2]

[0276] [Table 3]

[0277] [Table 4]

[0278] [Table 5]

[0279] [Table 6]

[0280] [Table 7]

[0281] [Table 8] [Explanation of symbols]

[0282] 10: Barrier laminate, 11: Multilayer substrate, 12: First vapor deposition film, 13: Adhesive layer, 14: Sealant layer, 15: Polypropylene resin layer, 16: Surface resin layer, 17: Second vapor deposition film, 18: Sealant substrate, 19: Barrier coat layer, 20: Adhesive resin layer, 21: Barrier laminate, 22: Multilayer substrate, 23: First vapor deposition film, 24: Adhesive layer, 25: Sealant layer, 26: Polypropylene resin layer, 27: Surface coat layer, 28: Second vapor deposition film, 29: Sealant substrate, 30: Barrier coat layer, 31: Packaging bag, 32: Standing pouch, 33: Body (side sheet), 34: Bottom (bottom sheet), 35: Easy-opening means, 36: No ch section, 37: half-cut wire, 38: steam release mechanism, 38a: steam seal section, 38b: non-seal section, 70: test piece, 71: substrate side, 72: sealant layer side, 73: gripping tool, A: vacuum vessel, B: unwinding section, C: film-forming drum, D: winding section, E: transport roll, F: evaporation source, G: reactive gas supply section, H: deposition protection box, I: deposition material, J: plasma gun, A1: vacuum vessel, B1: unwinding section, C1: cooling / electrode drum, D1: winding section, E1: transport roll, F1: glow discharge plasma, G1: reactive gas supply section, H1: raw material supply nozzle, I1: raw material gas supply section, J1: magnet, K1: power supply, L1: vacuum pump

Claims

1. A barrier laminate comprising a multi-layer substrate, a first vapor-deposited film, an adhesive layer, and a sealant layer, The multilayer base material is subjected to a stretching treatment, Furthermore, the multilayer base material has at least a polypropylene resin layer and a surface resin layer, The surface resin layer contains a resin material having a melting point of 180° C. or more, the resin material is an ethylene-vinyl alcohol copolymer, the barrier laminate has the first vapor-deposited film on the surface resin layer, the first vapor-deposited film is made of an inorganic oxide; A barrier laminate, wherein the sealant layer comprises a second vapor-deposited film and a sealant substrate.

2. The polypropylene resin layer and the sealant base material are made of the same material, 2. The barrier laminate according to claim 1, wherein the same material is polypropylene.

3. the second vapor-deposited film is an aluminum vapor-deposited film, 3. The barrier laminate according to claim 1, wherein the adhesive layer is an adhesive layer containing a cured product of a composition containing a polyester polyol and an isocyanate compound.

4. 4. The barrier laminate according to claim 1, wherein the resin material has a melting point of 265° C. or lower.

5. 5. The barrier laminate according to claim 1, wherein a difference between a melting point of the resin material and a melting point of the polypropylene contained in the polypropylene resin layer is 20 to 80° C.

6. 6. The barrier laminate according to claim 1, wherein a ratio of a thickness of the surface resin layer to a total thickness of the multilayer base material is 1% or more and 10% or less.

7. The barrier laminate according to any one of claims 1 to 6, wherein the multi-layer substrate is a co-extruded film.

8. A barrier laminate comprising a multi-layer substrate, a first vapor-deposited film, an adhesive layer, and a sealant layer, The multilayer substrate includes at least a polypropylene resin layer and a surface coating layer, The polypropylene resin layer is subjected to a stretching treatment, the surface coating layer contains a resin material having a polar group, the resin material is one or more resin materials selected from ethylene vinyl alcohol copolymer (EVOH), polyvinyl alcohol (PVA), polyester, polyethyleneimine, hydroxyl group-containing (meth)acrylic resin, nylon 6, nylon 6,6, MXD nylon, amorphous nylon, and polyurethane; the barrier laminate has the first vapor-deposited film on the surface coating layer, the first vapor-deposited film is made of an inorganic oxide; A barrier laminate, wherein the sealant layer comprises a second vapor-deposited film and a sealant substrate.

9. The polypropylene resin layer and the sealant base material are made of the same material, 9. The barrier laminate according to claim 8, wherein the same material is polypropylene.

10. the second vapor-deposited film is an aluminum vapor-deposited film, 10. The barrier laminate according to claim 8, wherein the adhesive layer is an adhesive layer containing a cured product of a composition containing a polyester polyol and an isocyanate compound.

11. The barrier laminate according to any one of claims 8 to 10, wherein a ratio of a thickness of the surface coating layer to a total thickness of the multilayer base material is 0.08% or more and 20% or less.

12. The barrier laminate according to any one of claims 8 to 11, wherein the surface coating layer has a thickness of 0.02 µm or more and 10 µm or less.

13. The barrier laminate according to any one of claims 8 to 12, wherein the surface coating layer is a layer formed using a water-based emulsion or a solvent-based emulsion.

14. The barrier laminate according to any one of claims 1 to 13, further comprising a barrier coat layer between the first vapor-deposited film and the adhesive layer.

15. The barrier laminate according to any one of claims 1 to 14, which is used for a packaging container.

16. A packaging container comprising the barrier laminate according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Laminate

    JP2001191462A

  • Aliphatic polyester film and packaging material

    JP2005053223A

  • Gas barrier film

    JP2006096046A

  • Multilayer barrier film, packaging laminate containing the film, packaging container formed from the packaging laminate, and method for manufacturing the film.

    JP2014531341A

  • Easily openable gas barrier laminate, and easily openable gas barrier packaging material and pillow packaging bag comprising the laminate

    JP2018171796A